2012
DOI: 10.1177/1358863x12442264
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine plus cilostazol versus cilostazol alone for the treatment of claudication in patients with peripheral artery disease: A multicenter, randomized, double-blind, placebo-controlled trial

Abstract: Intermittent claudication (IC) is the predominant symptom of peripheral artery disease (PAD), and is associated with reduced exercise capacity. The pathophysiology of IC is related to reduced blood flow and impaired skeletal muscle oxidative metabolism; however, the efficacy of metabolic therapies is not well established. We evaluated the effect of cilostazol plus l-carnitine versus cilostazol alone on exercise performance, quality of life (QOL), and safety. In a doubleblind, placebo-controlled trial, PAD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…This is the first study to demonstrate the functional improvement of the hindlimb following administration of cilostazol, L -carnitine, and their combination in experimental animals. Goldenberg et al [12] demonstrated that L -carnitine plus cilostazol used for the treatment of IC in patients with PAD improved walking performance compared to using cilostazol alone. This finding is consistent with our results, suggesting that the ischemic model and evaluation system used in this study is useful to examine the mechanisms of improvement of ischemic hindlimbs following the administration of cilostazol, L -carnitine, or their combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to demonstrate the functional improvement of the hindlimb following administration of cilostazol, L -carnitine, and their combination in experimental animals. Goldenberg et al [12] demonstrated that L -carnitine plus cilostazol used for the treatment of IC in patients with PAD improved walking performance compared to using cilostazol alone. This finding is consistent with our results, suggesting that the ischemic model and evaluation system used in this study is useful to examine the mechanisms of improvement of ischemic hindlimbs following the administration of cilostazol, L -carnitine, or their combination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that L -carnitine administration increased the walking distance in patients with PAD with IC [9][10][11] . In addition, it was demonstrated that the combination of cilostazol and L -carnitine improves IC in patients with PAD through enhanced angiogenesis secondary to increased VEGF levels and increased energy production, respectively [12] . VEGF production is, however, enhanced under ischemic conditions [13] .…”
mentioning
confidence: 99%
“…A series of 9 clinical trials (6 controlled trials) were reported testing CARN (or ALC, or PLC) in 359 patients with heart and vessel diseases [ 78 , 114 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. A study by McMackin et al [ 78 ] reported on the effects of combined ALC and ALA treatment in patients with coronary artery disease, and found significant improvement as increased brachial artery diameter, a trend to decreased systolic blood pressure for the whole patient group, with a significant effect in the subgroup with blood pressure above the median and in the subgroup with metabolic syndrome.…”
Section: L -Carnitine and Acetyl- Or Propionyl-mentioning
confidence: 99%
“…There are only very few published double-blind, placebo-controlled trials done in 2012 that evaluated the effectiveness of cilostazol/L-carnitine vs. cilostazol/placebo for 180 days [12]. Results demonstrated a trend for efficacy for the combination of these agents in patients with IC.…”
Section: Future Approachmentioning
confidence: 99%